Väderrestriktioner i hamnar - Eriksson, Alex; Silander, Johan (My University, 2016)
This study explains in a simple way how wind and waves are created and how view distance is affected by the amount of water in the atmosphere. It shows what systems are used today to measure the different factors and which authority is maintaining the specific systems, it also explains how pilots are using the information gathered by these systems to make proper decisions regarding safety of a vessel entering or exiting port with regards to the weather and currents. The information regarding restrictions decided by the harbours and what systems are available today were gathered from literature studies and the information from the pilots have been gathered through interviews. The information regarding systems in use have been gathered from the respective authority. The conclusion of the study shows that the system in use today are Bizmet, ViVa and GMFS. Bizmet gives the user access to forecasts in a specific area while ViVa is used to see the real time values of wind, current etc. GMFS is a model of the fairway leading to Gothenburg where the currents are modelled and the user can see the current at a specified depth and how it is going to change in the near future. The rules set in place depends on the length of the ship and the ship type in Gothenburg and on ship length in Stockholm. They are also there to protect the pilots from the hazards of boarding ships in bad weather. It is now easier than ever to acquire information since technology has developed at an astounding rate however it may lead to the user being unable to find a specific piece of information or the user may be overwhelmed by the sheer volume of information. There is a discussion regarding how the technology can be improved and how to gather all the information in one place without overwhelming the user. The problem with this is that the information will always be directed at a specific group and people not outside this targeted group may have trouble understanding the information correctly.
Keywords: Transportteknik och logistik; Transport; Transport Systems and Logistics; Transport